2018
DOI: 10.1002/2018gl077213
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variability of Magnetotactic Bacteria in a Freshwater Pond

Abstract: Magnetotactic bacteria (MTB) synthesize ferrimagnetic crystals that contribute to the remanent magnetization in sediments, yet knowledge of how MTB populations vary in natural environments over time remains limited. We report abundances of three MTB morphotypes from nine sites collected and measured every month over a two‐year period from a natural pond near Munich, Germany. Morphotype populations underwent coherent temporal trends among the nine sites—especially at proximal sites with similar water depths. MT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…According to their results, M rs /M s also reflects the relative abundance of magnetofossils to some extent. Similarly, He et al (2018) found that the M rs /M s increased with water depth due to an increase in magnetofossil concentration.…”
Section: 1029/2020gl087165mentioning
confidence: 76%
“…According to their results, M rs /M s also reflects the relative abundance of magnetofossils to some extent. Similarly, He et al (2018) found that the M rs /M s increased with water depth due to an increase in magnetofossil concentration.…”
Section: 1029/2020gl087165mentioning
confidence: 76%
“…Substrates were added immediately after sample collection. The sediments exhibited dynamic seasonal changes in total inorganic carbon (TOC) levels, with higher values in the summer (average, 10.09% ± 0.36%) than in the winter (average, 8.5% ± 0.22%) ( 47 ). The carbon-to-nitrogen ratio (C/N) is nearly constant in space and time (January 2015, 13.2% ± 0.8%; August 2016, 13.8% ± 1.3%; 1σ uncertainties) ( 47 ).…”
Section: Methodsmentioning
confidence: 99%
“…The sediments exhibited dynamic seasonal changes in total inorganic carbon (TOC) levels, with higher values in the summer (average, 10.09% ± 0.36%) than in the winter (average, 8.5% ± 0.22%) ( 47 ). The carbon-to-nitrogen ratio (C/N) is nearly constant in space and time (January 2015, 13.2% ± 0.8%; August 2016, 13.8% ± 1.3%; 1σ uncertainties) ( 47 ). The bottom water temperatures ranged from 13.6 to 18.5°C, 4.6 to 8.3°C, and 1.4 to 3.3°C in August, October, and December, respectively ( 47 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their abundance has been linked to paleo‐environmental and sedimentary conditions (Hesse, 1994; Kopp & Kirschvink, 2008; Maher & Hounslow, 1999; Roberts, Florindo, et al., 2011). Although it has been demonstrated that the number of living MTB undergoes seasonal changes (Du et al., 2015; He et al., 2018) and that magnetofossil abundance in deep‐sea sediments can be modulated by organic carbon and dissolved iron availability (Roberts, Florindo, et al., 2011) or by primary productivity (Savian et al., 2014), our understanding of the conditions responsible for MTB magnetic mineral formation is still limited.…”
Section: Introductionmentioning
confidence: 99%